SYPHILIS IN PREGNANCY - Gouveia, Ana Isabel (2014)
Syphilis is a systemic infectious disease with particular importance in pregnant women due to placental transmission to the fetus. Untreated syphilis during pregnancy can lead to serious consequences and long-term sequelae. Congenital syphilis remains a serious public health problem in many developing countries where prenatal screening and treatment programs are not effective. The number of cases of congenital syphilis is still high in Portugal compared with other European countries, which means that this infection is also common in adults. The consequences of this infection in pregnancy can be prevented by early universal prenatal screening and treatment, therefore efforts should be made towards improving care and access to prenatal care.